An Evaluation Of Short-Term Prognostic Significance Of Various Clinical Parameters In Patients Of Stroke - Saxena, Sonali; Khan, Shadab A; Saxena, Jalaj (Indian Journal of Community Health, 2006)
Sonali Saxena', Shadab A. Khan", Jalaj Saxena’" * Consultant Cardiologist, ** Professor (Medicine), *** Assistant Professor (Physiology) Ishwardevi Medical and Cardiology Centre, Kanpur J.N. Medical College, A.M.U., Aligarh and G.S.V.M. Medical College, Kanpur ABSTRACT: Objectives :To predict the short-term prognostic significance of various clinical parameters at the time of admission in patients of stroke. Setting: Department of General Medicine, J.N. Medical College, A.M.U., Aligarh Participants : 100 patients of stroke (Cerebro-vascular accident) comprising 54 males and 46 females. Clinical Parameters : Admission Blood Pressure, Side of paralysis, Extent of Paralysis, Gastro-intestinal Haemorrhage, Level of consciousness at the time of admission. Statistical Analysis: ‘Z’ test (Z>_ 1.96). Results : The admission B.P. was raised in 75% of patients. The mortality was significantly high (57.1%) in the severe grade B.P. while recovery was significantly high (64.3%) in mild or moderate grade B.P patients. The left sided paralysis was having significantly high mortality of patients (49%) while recovery was significantly high (56.2%) in the patients with right sided paralysis. The paralysis with Grade O power was in 58% of stroke patients and was associated with significantly high (53.4%) mortality while 100% recovery was found in patients with power grade 4 and 5 at the time of admission. The G.l. haemorrhage was associated with 5% of patients but mortality was significantly high (100%) in these patients. The level of consciousness of grade / was highest (34%) while mortality was significantly high (100%) in the patients admitted with grade 3 level of consciousness. The recovery was significantly high (92.9%) in the patients admitted with grade 'O’ level of consciousness